Writing for Readability - Kirk, Ken; American Society for Training and Development (Infoline, 2010)
This Infoline will tackle the readability issue more appropriately by discussing guidelines for mastering clear and concise sentences in your workplace writing. The goal is to practice composing a sentence that requires only one reading to decipher the intended message. In this Infoline, you will learn strategies to tighten and simplify your sentences; eliminate wordiness and redundant phrasing; and build a vocabulary to help your co-workers revise their work.
Keywords: Business writing; Report writing; Writing